Predicting difficulties of Ilocano learners in the use of English simple primary conjunctions a descriptive-contrastive analysis - Raymundo, Federico A. 1928- ([s.n.], 1971)
The over-all objective of this study is to find out the sources of problems in learning the English simple primary conjunctions among Ilocano learners of English in Grades V and VI of the randomly selected complete elementary schools of Laoag, Northwest District, Laoag City, Division of Ilocos Norte. The investigator used the descriptive-contrastive method in predicting the difficulties of Ilocano children in the use of the English simple primary conjunctions. Whitehall's method of description and Lado's steps of comparison were adapted in this research.